Tangled up in Texas - Fossen, Delores (Fossen, Delores. Lone Star Ridge., 2020)
Their past never faded -- and neither did their passion. Between running his family ranch and dealing with far too many needy relatives, Shaw Jameson doesn't have time for more trouble. But when his first love, former-child-star-turned-businesswoman Sunny Dalton, returns to Lone Star Ridge, Shaw senses things are about to get a whole lot more interesting. Shaw isn't prepared for the memories that come flooding back now, or the reignited spark between them that turns into a raging inferno. Still, this gorgeous cowboy will do everything he can not to get burned a second time. Because Sunny never promised this visit was permanent and Shaw has no intention of giving up the land he loves. Letting Sunny go again is certain to leave a Texas-sized mark on his soul, and a permanent wall around his heart. Unless he can prove their small town holds the promise of the future they both always imagined.